PENGARUH TEKNOLOGI INFORMASI TERHADAP MAHASISWA AKUNTANSI DI UNIVERSITAS 17 AGUSTUS 1945 SURABAYA - Claudya Sizika Beatrix Syaiful; Hwihanus, Hwihanus (Cahaya Ilmu Bangsa, 2024)
The development of information and communication technology is now increasingly advanced and has penetrated all lines of life regardless of status, whether old or young, poor or rich, all have been infected by the epidemic of the development of information and communication technology. with the development of information and communication technology, it has both positive and negative impacts, this is in accordance with research conducted by (Setyoningsih, 2015). With the development of information and communication technology, it also greatly helps the world of education, especially making it easier to search for data and information related to research topics and in making assignments, making or final project proposal papers, students will very easily get the topics or themes they are looking for in minutes or even seconds. The purpose of this study is to find out how information technology affects accounting students at the University of 17 August 1945 Surabaya. using qualitative methods with questionnaires and collecting respondents. The qualitative approach was chosen because the main purpose of the study is to detail and understand more deeply about information technology, especially the influence of information technology. The influence of information technology in students' lives has turned out to be quite helpful for them in the learning process, preparation of financial reports and the effectiveness of their learning. However, there are several risks, namely that students tend to look for answers on the internet rather than think critically.